Poodle
Answered

Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

If f(x)=5x^3-2 and g(x)=2x+1, find (f+g)(x).

Sagot :

[tex](f+g)(x)=f(x)+g(x)\\\\ (f+g)(x)=5x^3-2+2x+1\\ (f+g)(x)=5x^3+2x-1[/tex]